Experimental and Theoretical Analysis of Hollow Steel Columns Strengthening by CFRP - Amir Hamzeh Keykha; Masoud Nekooei; Reza Rahgozar (Institute of Research and Community Outreach - Petra Christian University, 2015)
The need for strengthening and retrofitting is well known and extensive research is progressing in this field. The reasons for strengthening and retrofitting are numerous: increased loads, changes in use, deterioration, and so on. In recent years, the use of carbon fiber reinforced polymer (CFRP) for strengthening has shown to be a competitive method, both regarding structural performance, and economical aspects. Extensive research has been carried out in this field. However, most of the research has been undertaken on concrete structures and for confinement, flexural, and shear strengthening. Limited research has been carried out on steel structures strengthened with CFRP. This paper presents axially loaded steel columns strengthened for increased load. The topic is studied theoretically and through laboratory tests. The theory covers analytical methods. Carbon fiber reinforced polymers has been used to strengthen the columns. The tests have been undertaken on full scale specimens, non-strengthened for reference, partially strengthened and fully strengthened